Upaya Meningkatkan Perencanaan Karir Siswa Melalui Bimbingan Karir dengan Penggunaan Media Modul - Atmaja, Twi Tandar (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2014)
One of the tasks the development of high school teenagers are prepared to face the world of work or career. This study aims to improve students career planning through career guidance with the use of media modules in class XII IPA 2 MAN Wonokromo Bantul academic year 2013/2014. This research is action research. The subjects were taken in this study using purposive sampling as many as 12 students who have a low level of career planning. Methods of data collection using questionnaires and observation. Analysis of the data used using the formula t-test to see the differences between the mean pretest and posttest mean. The research shows students career planning class XII IPA 2 can be enhanced through the use of media career guidance module seen from the significant difference from the average prior to career guidance at 105.25 and after a mean of 122.50 and career guidance. It can be concluded "there is increasing career guidance, career planning through the use of media modules in class XII IPA 2 MAN Wonokromo Bantul academic year 2013/2014. The results of this study can be used as reference material for teachers bmbingan and counseling programming and media development of career counseling services to improve students career planning.